Analysis of Handling State Losses In Corruption Crimes - Mulyono Mulyono; Eny Maryana (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Handling of corruption offenses. Article 4 of Law No. 31 of 1999 states that